Professionalism as a Generalized Typical Model of a Professional in the Higher Education System; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Latygovskaya T. P. Tatiana Petrovna (2015, 2015)
Title screen